Peripheral focused ultrasound stimulation and its applications: From therapeutics to human–computer interaction - Bao, Shi-Chun; Li, Fei; Xiao, Yang; Niu, Lili; Zheng, Hairong (Frontiers in Neuroscience, 2023)
Peripheral focused ultrasound stimulation (pFUS) has gained increasing attention in the past few decades, because it can be delivered to peripheral nerves, neural endings, or sub-organs. With different stimulation parameters, ultrasound stimulation could induce different modulation effects. Depending on the transmission medium, pFUS can be classified as body-coupled US stimulation, commonly used for therapeutics or neuromodulation, or as an air-coupled contactless US haptic system, which provides sensory inputs and allows distinct human-computer interaction paradigms. Despite growing interest in pFUS, the underlying working mechanisms remain only partially understood, and many applications are still in their infancy. This review focused on existing applications, working mechanisms, the latest progress, and future directions of pFUS. In terms of therapeutics, large-sample randomized clinical trials in humans are needed to translate these state of art techniques into treatments for specific diseases. The airborne US for human-computer interaction is still in its preliminary stage, but further efforts in task-oriented US applications might provide a promising interaction tool soon.